Problématique d'aménagement sylvopastoral au Maroc. Cas du projet d'aménagement sylvopastoral de la forêt de la Mamora - Naggar M. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
The forest of Mamora occupies about 69000 ha. This forest integrates multi-purpose systems such as production of wood, cork, forage and secondary products (mushroom and honey). The technical, social and economic studies realised in Mamora, has permitted to show the multiple constraints in this forest: Overgrazing, the mean pastoral stoking rate is 6,4 sheep unit/ha, and the pastoral production is less than 400 feed units/ha; beating and topping of cork oak in dearth periods; lack of natural regeneration of cork oak because of gathering acorns and overexploitation of pasture land in Mamora by forest users; lack of farmers' supervision and organisation. Consequently, the forest management in Mamora should integrate new conditions of users participation in an economically viable option to regenerate the resources of woodland and rough pasture, and thus develop stock raising in the Mamora region.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)